High-Frequency Repetitive Transcranial Magnetic Stimulation Mediates Autophagy Flux in Human Bone Mesenchymal Stromal Cells via NMDA Receptor–Ca2+–Extracellular Signal-Regulated Kinase–Mammalian Target of Rapamycin Signaling - Wang, Xinlong; Zhou, Xing; Bao, Jie; Chen, Zhiguo; Tang, Jingzhao; Gong, Xueyang; Ni, Jing; Fang, Qi; Liu, Yaobo; Su, Min (Frontiers in Neuroscience, 2019)
Repetitive transcranial magnetic stimulation (rTSM) is a non-invasive and safe technique for treatment of central and peripheral nerve injury. In recent years, this technique has been widely used in the clinic and an increasing number of studies have reported its mechanisms. In this study, we investigated the mechanisms of rTMS mediated autophagy flux in human bone mesenchymal stromal cells (BMSCs). Methods: A frequency of 50 Hz was employed. Cells were divided into five groups: (1) normal; (2) sham; (3) 0.5 T; (4) 1.0 T; and (5) 1.5 T. Cells were stimulated for 20 minutes per day. The levels of p62, LC3-II/I, p-ERK, ERK, p-AKT, AKT, p-mTOR, mTOR, p-PKA, PKA, p-EGFR, EGFR, Nanog, Oct4, Sox2 and NMDAR1 were investigated by western blotting. Intracellular calcium (Ca2+) levels were quantified by flow cytometry. p62 and LC3 expression were also assessed by immunofluorescent analysis. Results: In the 0.5 T group, rTSM increased the expression of LC3-II/I, p-ERK/ERK, NMDAR1, and decreased the levels of p62 and p-mTOR/mTOR compared to the normal group. The ratio of p-AKT/AKT, p-PKA/PKA and p-EGFR/EGFR and the expression of Nanog, Oct4 and Sox2 remained unchanged. Immunofluorescence analysis revealed colocalization of p62 with LC3 puncta and flow cytometry analysis displayed Ca2+ levels were elevated. However, in the 1.0 T and 1.5 T groups, no changes in the expression of these autophagy markers were observed. Conclusions: In the 0.5 T group, high-frequency rTSM can induce autophagy through NMDAR–Ca2+–ERK–mTOR signaling in BMSCs. In the 1.0 T and 1.5 T groups, autophagy is not activated.